XIMIYA SABAQLARÍN OQÍTÍWDA DIDAKTIKALÍQ OYÍNLARDAN PAYDALANÍW - Aymurzaeva, L.G. (SCIENCE and SOCIETY, 2025)
The article examines the teaching of the theory of electrolytic dissociation in chemistry classes using didactic games. When learning with the use of didactic games develops rapid thinking ability of students, clear expression of thought, culture of chemical language, increases creativity and activity of students.